Measuring eco - tourist perception, knowledge, acceptance and revisit intention in malaysia - Summeta A/P Sugumarn; Siti Sarah Shamsuddin; Sukphin A/P Eh Boon; Syamimi Aziz (2023)
The purpose of this study is to identify various problems found in various sectors of ecotourism. Most of them are problematic about community thinking, lack of understanding about ecotourism activities, lack of facilities, and so on. The objective of this study is to study the influence of ecotourism according to perception, knowledge, and acceptance on the intention to revisit Malaysia. As for that, the quantitative methodology is used in this study. The simple size sampling is used as a sampling frame. The total number of 150 respondents were targeted and analysed using the Statistical Package. The result from this study is to measure eco tourist perception, knowledge, acceptance, and revisit intention in Malaysia. The finding from this research is plausibility to engage for the future research. This study will be beneficial to appreciate the nature and knowledge while research has been done. Practitionery among people can be gained to appreciate the nature place when they can get knowledge and acceptance towards to take care eco-tourist place in Malaysia.